A Systematic Literature Review of GeoGebra Implementation in Project-Based Learning - Sidhik Hidayatullah; Isti Hidayah (Southeast Asian Journal on Open and Distance Learning, 2025)
The objectives of this study are to analyze how GeoGebra has been implemented in Project-Based Learning ( PjBL ) models within mathematics education, to explore the effectiveness of its integration in improving learning outcomes, and to provide insights for future pedagogical approaches involving dynamic mathematics software. This study employed a Systematic Literature Review (SLR) method following the PRISMA protocol to ensure rigorous and transparent article selection and synthesis. The search process involved filtering 428 articles published between 2020 and 2025 using three major academic databases: Google Scholar, Scopus, Semantic Scholar, and Crossref. A final set of 21 articles was selected for in-depth review and analysis based on relevance to the research questions and inclusion criteria. The findings indicate that integrating GeoGebra into PjBL positively enhances students' conceptual understanding, mathematical reasoning, and engagement. Most studies also highlight the role of GeoGebra in facilitating interactive, student-centered learning environments. This review provides evidence-based recommendations for educators and researchers aiming to optimize the use of GeoGebra in project-based learning contexts. It contributes to the growing body of literature supporting the strategic use of digital tools in mathematics education.